Food-based indices for the assessment of nutritive value and environmental impact of meals and diets: A systematic review - Eva-Leanne Thomas; David Livingstone; Anne P. Nugent; Jayne V. Woodside; Leona Lindberg; Paul Brereton (PLoS ONE, 2026)
Food production and consumption impact both human and planetary health. Clearly conveying how meals and diets influence nutritional adequacy and environmental sustainability is essential for informed decision-making among consumers. This systematic review identifies and examines existing food-based indices that classify or rank meals and diets based on both nutritive value and environmental impact, that the authors termed Nutritive and Environmental Combined Indices (NECIs). Following PRISMA 2020 guidelines, six bibliographic databases were searched in August 2025 using four search concepts: nutrition, environment, index, and meal/diet. Studies assessing both nutritive value and environmental impact of meals or diets, published between January 2009 and August 2025, were included. Two independent reviewers screened studies and extracted data on NECI characteristics. The review protocol was registered with PROSPERO (CRD42024537149). Twenty-five NECIs, presenting 27 methodological approaches, were identified: six specific to meals, nine for diets, and ten offering scope to be applied to either. Nutritive and Environmental Combined Indices varied widely in scoring methods, with 13 different nutritional and six different environmental scoring approaches. Presentation formats also differed: 19 used a single integrated metric, four reported scores in parallel, and two used both. Additionally, 12 NECIs considered other dimensions of sustainability, primarily economic (n = 10) followed by socio-cultural (n = 6). Among integrated NECIs, variations were observed in dimension weighting, methodological approaches, and ranking criteria. A strength of this review is its focus on NECIs beyond individual food products, assessing their applicability to meals and diets. The review synthesises factors such as nutritional and environmental scoring methodologies, functional units, system boundaries, composite scoring techniques, weighting approaches, index scoring frameworks, and databases used. However, significant methodological variation among NECIs posed challenges for direct comparison. These findings provide a foundation for the development of standardised NECIs, supporting public health efforts to promote healthy and sustainable meal and diet choices.